The Psychodynamic Image : John D. Sutherland on Self in Society. - Savege Scharff, Jill (Taylor and Francis, 2014)
The Psychodynamic Image is the first selection of John D. Sutherland's major papers. It provides an overview of the development of his thought on self and society and reveals the extent of his contribution to the field of mental health. Jill Savege Scharff introduces Sutherland's most important and influential essays. These reflect his range as a theoretician, moving easily from the intrapsychic to the interpersonal level, building bridges between points of view and integrating psychoanalytic and social theories. Sutherland's work calls for changes at the individual level.